Relational Dialectics of Women's Identity in the Colonial Era in RA Kartini's Letters - M Khairullah; Nina Yudha Aryanti; Tina Kartika; Abdul Firman Ashaf; Purwanto Putra (SAINTIS Publishing, 2025)
This article analyzes the construction of women's identity through a relational dialectics approach implied in the letters of RA Kartini. With the context of Dutch colonialism and the dominance of Javanese patriarchal culture, the letters became an arena of discourse where Kartini constructed her identity as a modern Javanese woman. This research uses library methods on Kartini's correspondence in the book Door Duisternis tot Licht (Habis Gelap Terbitlah Terang) and relevant archives. The analysis results show that Kartini not only fought for women's emancipation but also deconstructed the passive identity imposed on indigenous women by crafting a strong narrative of cultural resistance. The dialectic between Western values and local traditions creates complexity in her narrative of identity as a colonial woman.